Εξ αποστάσεως μουσειακή εκπαίδευση στην προσχολική αγωγή. Έρευνα Δράσης: Η δημιουργία ενός εικονικού μουσείου στο νηπιαγωγείο; Distance Museum Education in pre-school education. Action Research: The creation of a virtual museum in pre-school. - Μουρατίδου (Mouratidou), Όλγα (Olga); Μανούσου (Manousou), Ευαγγελία (Evangelia) (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2020)
Η εξ αποστάσεως εκπαίδευση είναι η νέα τάση που επικρατεί τα τελευταία χρόνια στο χώρο της παιδείας και υπόσχεται να καλύψει τις σύγχρονες ανάγκες των μαθητών, σύμφωνα με τα ζητούμενα της νέας εποχής της Κοινωνίας της Γνώσης και της Πληροφορίας. Τη σημασία της εξ αποστάσεως εκπαίδευσης, και κάποιες από τις δυνατότητες της τις βιώσαμε ιδιαίτερα, την περίοδο της πανδημίας, όπου μια νέα εφαρμογή της, που ονομάστηκε «επείγουσα» εξ αποστάσεως εκπαίδευση, αποτέλεσε τη βασική επιλογή για τη συνέχιση της εκπαίδευσης, με όλες τις ιδιαιτερότητες και τις δυσκολίες που αναδείχθηκαν. Ωστόσο για την εφαρμογή της στην προσχολική ηλικία υπάρχουν ελάχιστα ερευνητικά δεδομένα και πληροφορίες. Η παρούσα εργασία στοχεύει στη μελέτη των αποτελεσμάτων της εφαρμογής της συμπληρωματικής εξ αποστάσεως μουσειακής εκπαίδευσης στο νηπιαγωγείο επιχειρώντας ταυτόχρονα τη δημιουργία ενός εικονικού μουσείου που θα βασίζεται στα ενδιαφέροντα και στη συμμετοχή των παιδιών στο πλαίσιο της εφαρμογής αυτής. Για τον σκοπό αυτό αξιοποιήθηκε η έρευνα δράσης στην οποία συμμετείχαν δώδεκα νήπια του ολοήμερου τμήματος νηπιαγωγείου καθώς και η εκπαιδευτικός-ερευνήτρια. Η συλλογή δεδομένων στο πλαίσιο της έρευνας δράσης έγινε με τρεις διαφορετικές μεθόδους (συνέντευξη, παρατήρηση, ημερολόγιο) και πηγών (γονείς, μαθητές, κριτικοί φίλοι). Τα αποτελέσματα της έρευνας κρίνονται θετικά τόσο για το νηπιαγωγείο όσο και για όλα τα εμπλεκόμενα μέλη (μαθητές, γονείς, εκπαιδευτικούς). Η μαθησιακή εμπειρία των παιδιών εμπλουτίστηκε με ένα πιο σύγχρονο μαθησιακό περιβάλλον μέσα στο οποίο καλλιέργησαν νέες χρήσιμες και σύγχρονες δεξιότητες, απέκτησαν καινούργιες γνώσεις, ανέπτυξαν τη δημιουργικότητα και τη κριτική τους σκέψη και διαμόρφωσαν θετική στάση απέναντι στα μουσεία; Distance Education is the new trend which prevails in the field of education in recent years, which undertakes to cover the contemporary needs of students, according to the requirements of the new era of Information and Knowledge Society. We especially experienced the significance of Distance Education, and some of its potentials, during the period of the pandemic, when a new application, which was defined as “urgent” Distance Education, constituted the main choice for the continuation of education, along with all the particularities and difficulties that emerged. Nonetheless, there are few research data and information as to its application in the pre-school age. The present project aims to study the results of the implementation of Complementary Distance Museum Education in pre-school, attempting concurrently to create a virtual museum, which will be based on the interests and participation of children in the framework of this implementation. The research inquiries which framed the particular project relate to which requirements have to be fulfilled through the Complementary Distance Education so that it can be implemented in pre-school age, how the Complementary Distance Museum Education can contribute to the education of pre-school children and in what way Technology of Information and Communication can be deployed in Complementary Distance Museum Education in pre-school education. For this purpose, Action Research was deployed, as the educator- researcher scrutinizes the results of the implementation of a new program and attempts to find solutions to a problem. In the case of the present project, the problem arises from the difficulty in accessing the local museums and the sites of cultural inheritance in general, in Greece and abroad. The implementation of an innovative Distance Museum Education program along with a creative use of Technology of Information and Communication could be the solution to our problem. In addition, we need to highlight that after our self-reflection during the pandemic period, closed schools and museums, and the “urgent” Distance Education offered a new perspective and stressed the importance of Distance Museum Education in pre-school even more. To ensure the validity of the research the following were observed: an exhaustive relevant literature review, planning of an appropriate schedule, use of a representative sample, deployment of appropriate methodology/research tools and use of sufficient sources. Based on the principles of triangulation, the data was collected with the use of various methods, such as: a research diary was kept by the educator- researcher throughout the data recording process, resulting from the observation of children, the discussions/ interviews and the educators personal thoughts, observation – direct non-participant observation was deployed from the researcher and the critical friend for data collection , semi-structured interview- realized to record the thoughts and opinion of the critical friend in relation to the implementation of Distance Museum Education following the realization of the program, group discussions/ interviews- with this method the children’s opinions on their experiences from the program implementation were collected, questionnaire - for the probe of parent’s opinions on the results of Distance Museum Education implementation in pre-school. Twelve pre-school children of the all-day kindergartner participated in the research, as well as the educator- researcher, a colleague kindergartner teacher and the children’s parents. The Action Research was implemented in a single-seat kindergartner of a village on Ikaria Island. In the specific kindergartner, during the school year 2017- 2018 – that is before the pandemic - two pre-school teachers served in the morning zone and afternoon zone respectively. The all-day program was assigned to the educator- researcher for the duration of the school year. The colleague of the morning zone assisted the researcher in the research and took the part of the critical friend. For the participation of the children in the research, parents were asked to sign the parental consent form, after briefing. In a group discussion, the children’s previous knowledge about museums was scouted and recorded in a concept map. From the recording of children’s previous knowledge, it was ascertained that the children have little to no knowledge and experience on museums. That was the incentive to initiate the Museum Education program, and given that our school is in the borderline, far from the great museums of the city and the world, we decided to exploit all the potentials of Distance Education and Technology of Information and Communication. In the beginning, we saw pictures/ photos of museums on the computer, then we searched for information on the Internet about museum professions and the types of the museums, we visited museums “virtually”, we contacted via Skype the manager of the Toy Museum in Ermioni and finally, we created our own virtual museum with the help of the Art steps program. Since the subject of the program was defined, the educator- researcher planned developmentally appropriate activities based on the needs and interests of the children. The activities mainly dealt with the engagement of the children with the computer and the Internet for two hours a day. The educator- researcher has created the necessary software shortcuts and the photo folders on the desktop to ensure easy access for the children and has also cared for the children to work in pairs when they use the Technology of Information and Communication. The pre-school children had the chance to work autonomously, to browse around the museums virtually, to play, to observe the objects, to peer at them virtually (to enlarge them, minimize them, to look inside e.t.c.). The children also had the opportunity to create their own virtual museum, putting up pictures of toys on a virtual display. The creation of a virtual museum by the children consisted the amazing action of the program since they were able to apply all the knowledge they gained during the educational intervention. During free activities, the children could visit their own museum or whichever museum they desired and as many times as they wanted to depending on their interests to select their own course and engagement rate. The results of the research are thought to be positive both for the kindergartner and all the parts involved (students, parents, educators). The children displayed a great interest in the program and learned new things. In particular, we noticed that the children approached the concept of the modern museum, they realized that it is not just a place that keeps old objects but it offers several social services, they also understood the importance of cultural inheritance and its significance for the modern man, the benefits and the role of Technology of Information and Communication in Distance Museum approach. The children also acquired a positive attitude towards museums and were looking forward to visit them live. The parents also proved to be staunch supporters of the action, they filled in the evaluation of the action questionnaire willingly, and they often briefed on the children’s impressions when returning home. All parents expressed a positive opinion on the specific program and they believe that it would be nice to implement such programs or equivalent programs that bring children in touch with the society and their culture. The particular research showed that interactive creative activities, such as virtual tours in museums, the creation of a virtual museum, interactive games/ applications on museum sites, as well as modern communication through teleconference with the museum manager, apply to the principles of distance school education and can contribute to pre-school children’s learning experience. The prerequisites of Distance Museum Education implementation totally comply with the basic principles of learning , as it employs a multiform material (image, sound, text, video), it supports multiple forms of learning (autonomous, experiential, collaborative, multi-sensory, learning through play), it enables skills cultivation( creativity, critical thinking e.t.c) , it is based on the child’s interests and respects their individual learning rate. Distance Museum Education, along with its implementations, is likely to cover the needs of children who live far from museums. Furthermore, as the article was completed during the period of the pandemic, it has given us the opportunity, with the help of our self-reflection, to discover that Distance Museum Education could potentially consist an outstanding, authentic, qualitative, effective and substantial learning activity, even in the “urgent” distance education, in the pandemic period.